(3GdeHge Ydi MQha GdeYLes - (3jMji Hf TQa Hf oepqQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf,J (B676 (3g` s ((3eMeO Hf Ydi GdTgjQ HEeGe efLc s)
(3ChdgG (B:s
(3hHYO aEf Yde GdMOjK ef CfaS GdYdhe GdTQYjI hef LedI Ydheg GdRGgGQJ eYQaI eG jbY ai eJhfg ef GdCSeGA hGdeHgeGJ s
(3BNQgG (B:s
(3hgPG GdHGH hGSY LOkG , hajgG CTQJ caGjI aigPG GdcJGH agPG BNQ eG JjSQ hMSHfG Gddg hfYe Gdhcjd s
(3HgG fXGe GdJYbjHIs
(3bQCgG GdfGSN Ydi CHj HcQ eMeO Hf YHO Gddg Hf CMeO Hf GdeMH ai efRdg HGdeOQSI GdVjGFjI HSaM bGSjhf ai GdSfI faSgGs
(3cJHgG GdfGSN dfaSg s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs